Pendampingan Pembuatan Aplikasi Sistem Pembayaran Digital (Qris) Pada Umkm Toko Kelontong - Avid Tri Asih; Ika Wulandari (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Community service activities aim to increase understanding and knowledge about digital or non-cash payment systems. This service was carried out at the MSMEs of the